The Role of Social Companion Competence in the Effectiveness of Social Welfare Assistance Distribution - Eko Lianto Rihardi (CV. Sutan Mandiri Sejahtera, 2026)
The distribution of social welfare assistance often faces challenges in targeting accuracy and efficiency in the field. Social workers play a crucial role as the spearhead of the program, and their capacity and expertise are strongly suspected of influencing its success. This study aims to analyze and explain the influence of social worker competency on the effectiveness of social welfare assistance distribution. This study aims to analyze and conceptualize the role of social worker competency on the effectiveness of social welfare assistance distribution based on various scientific literature and related regulations. This study used a qualitative approach with a library research method. Data sources were obtained from books, accredited scientific journals, official reports, and government regulations relevant to the theme of competency and social assistance. Data collection techniques were conducted through documentation and literature review. The results indicate that social worker competency, encompassing cognitive dimensions (knowledge of regulations and digital systems), psychomotor skills (communication, advocacy, and conflict mediation skills), and affective (a work attitude based on integrity and empathy), significantly influences the program's success as a key variable. The integration of these three competency dimensions has been proven to realize the principle of the five rights (targeting, quantity, timeliness, quality, and administration) and reduce horizontal conflict in the community. In conclusion, the effectiveness of social assistance distribution is largely determined by the professionalism and competency of the field facilitators. This study recommends standardizing periodic training curricula and implementing professional certification for social workers by relevant agencies to maintain the quality of assistance